Initial Products and Reaction Mechanisms for Fast Pyrolysis of Synthetic G‐Lignin Oligomers with β‐O‐4 Linkages via On‐Line Mass Spectrometry and Quantum Chemical Calculations. Issue 24 (22nd August 2017) - Sheng, Huaming; Murria, Priya; Degenstein, John C.; Tang, Weijuan; Riedeman, James S.; Hurt, Matthew R.; Dow, Alex; Klein, Ian; Zhu, Hanyu; Nash, John J.; Abu‐Omar, Mahdi; Agrawal, Rakesh; et al.
Abstract: The products of fast pyrolysis that first leave the hot pyrolysis surface were identified for three G‐lignin model compounds, a trimer, a tetramer and a synthetic polymer, all containing β‐O‐4 linkages, by using a very fast heating pyrolysis probe coupled with a linear quadrupole ion trap mass spectrometer or a linear quadrupole ion trap coupled with an orbitrap detector. High‐resolution measurements were used to determine the elemental compositions of the deprotonated pyrolysis products. Their structures were examined using collision‐activated dissociation experiments and via comparison to the dissociation reactions of ionized authentic compounds. The initial pyrolysis products for all model compounds range from monomers to tetramers. Even for the polymer, no products larger than tetramers were observed. None of the products were radicals. The observed trimers and tetramers were formed directly from the intact model compounds rather than from repolymerization of initially formed monomers. Both the observed product distributions and quantum chemical calculations suggest that the mechanism(s) of the major reactions occurring under the conditions employed here are Maccoll and/or retro‐ene eliminations rather than radical reactions. Based on a comparison of the behavior of the smaller β‐O‐4 model compounds to the synthetic β‐O‐4 lignin polymer, the smaller model compounds appear to be good surrogates for further studies of the mechanisms of fast pyrolysis of lignin. Abstract : The initial fast pyrolysis products of three β‐O‐4 G‐lignin model compounds were identified using a very fast heating pyrolysis probe coupled with ion trap mass spectrometry. High‐resolution measurements were used to determine the elemental compositions of the deprotonated pyrolysis products. Their structures were examined by using collision‐activated dissociation experiments. The observed product distributions and quantum chemical calculations suggest that the mechanism(s) of the major reactions occurring under the conditions employed here are Maccoll and/or retro‐ene eliminations rather than radical reactions.